Temperature-Independent Polarization of Ultrathin Phthalocyanine-Based Hybrid Organic/Inorganic Heterojunctions - Silva, Ricardo M. L. [UNESP]; Merces, Leandro; Bof Bufon, Carlos C. [UNESP] (American Chemical Society (ACS), 2020)
The combination of organic and inorganic materials at the nanoscale to form functional hybrid structures is a powerful strategy to develop novel electronic devices. The knowledge on semiconductor thin-film polarization brings direct benefits to the hybrid organic/inorganic electronics, becoming primordial for the development of devices such as electromechanical logic gates, solar cells, miniaturized valves, organic diodes, and molecular supercapacitors, among others. Here, we report on the dielectric polarization of ultrathin organic semiconducting films-ca. 5 nm thick metal phthalocyanine ensembles (viz., CuPc, CoPc, F16CuPc)-employed to build up hybrid metal/oxide/molecule heterojunctions. Such hybrid heterostructures are fully integrated into self-rolled nanomembrane-based capacitors and further investigated by impedance spectroscopy measurements as a function of temperature (from 6 to 300 K). The dielectric polarization of the metal phthalocyanines is found to be thermally activated above a specific threshold temperature, which depends on the molecular structure. Below this threshold, the current leakage across the system is suppressed, thus evidencing intrinsic-like polarization mechanisms. The temperature-independent permittivities of the ultrathin molecular films are found to be strongly dependent on the organic/inorganic hybrid interfaces, while the calculated relaxation times are more likely related to each single-molecule polarization. Beyond the advances in determining the temperature dependence of the permittivity for ultrathin phthalocyanine films integrated within solid-state electronics, our results also support the deterministic design of novel functional devices based on nanoscale hybrid organic/inorganic heterojunctions.
Keywords: dielectric polarization; hybrid electronics; molecular ensembles; nanomembranes; organic semiconductors